Investigating the current state of the Russian market for drugs treating infectious and inflammatory conditions of oral cavity and oropharynx to demonstrate the need for new drug development - V. I. Zvereva; D. R. Dzhavakhyan; V. N. Dul; V. S. Bobyleva; A. A. Markaryan; E. I. Morkovin; D. V. Kurkin; M. A. Dzhavakhyan (IRBIS LLC, 2024)
Objective: to assess the relevance and commercial prospects of bringing to market a drug for the local treatment of infectious and inflammatory diseases of oral cavity and oropharynx.Material and methods. The objects of the study were the drug nomenclatures in the State Register of Medicines, the Register of Medicines of Russia, as well as data from the Federal Service for Surveillance in Healthcare. The analysis of scientific publications in the field of marketing research of drugs, found in eLibrary.ru and PubMed/MEDLINE databases was carried out. For analyzing the structure and marketing research of drugs in the study group, specific methods of information retrieval, content analysis, description, data aggregation, ranking, data grouping method, system approach, as well as such methods of marketing analysis as determining the breadth and depth of the assortment, the renewal index, the vital importance index, SWOT analysis (strengths, weaknesses, opportunities, threats) were used.Results. The assortment of drugs for the local treatment of oral cavity and oropharyngeal infectious and inflammatory diseases was structured by the nature of the active substance, type of dosage form, and country of origin. The main trends in the development of the market of drugs of this group were identified. An analysis of the range of drugs using marketing research methods made it possible to establish the breadth and completeness of the range. The calculated renewal and vitality indices confirmed the relevance of developing new drugs with the considered pharmacotherapeutic action.Conclusion. The study revealed the main trends in the development of the market of drugs of the action in question. The SWOT analysis showed a possible strategy for developing and launching a new drug on the market.